ANALISIS MEKANISME PENETAPAN UPAH MINIMUM PROVINSI JAMBI TAHUN 2015 - Syarifa Mahila (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
In the process of policy formulation Provincial Minimum Wage (UMP), Component Living is one of the decisive factors for the quantitative factors . UMP indispensable mechanism for setting a negotiation between members of wages councils to obtain consensus decisions .Proposed Determination process UMP Jambi Province conducted by ballot because no agreement was reached by consensus. A majority vote , the proposal UMP Jambi 2015 amounted Rp.1.710.000 . (One Million Seven Hundred Ten Thousand) .Keywords : KHL , UMP , Wage Council .